Side Effects of Medical Cancer Therapy Prevention and Treatment (Springer International Publishing, 2018)
This is the second edition of a well-received book that reflects the state of the art in cancer medical therapies and their side-effects, including immunotherapy and chemotherapeutic drugs. All chapters have been fully updated to include all the latest progress in drug discovery such as targeted therapies for each cancer type. From issues such as preservation of fertility to antiemetic therapy the book provides a very comprehensive overview of the field. The book includes a new chapter on immuno-oncology drugs. Organised by organ system, it lists the toxicity, side-effects and measures of prevention pertaining to each type of drug used in cancer therapy. The most dangerous side-effects are priority so as to alert the reader to their importance. Designed for quick reference in the clinical setting this book is primarily aimed at established medical oncologists but will also appeal to junior doctors, trainees, pharmacists and nurses.